The Analysis of the Effect of Perceived Marketing Mix and STP Strategies on Customer Satisfaction: A Case Study of Heytea in China - Lu Ao; Trianasari; Ni Made Ary Widiastini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid growth of China’s new-style tea beverage industry has intensified market competition, making customer satisfaction a crucial determinant of business sustainability. In this highly dynamic environment, tea beverage brands must not only adopt effective marketing strategies but also ensure that their strategic and operational decisions align with customer expectations. This study aims to examine the effect of perceived marketing mix and Segmentation, Targeting, and Positioning (STP) strategies on customer satisfaction, using HEYTEA as a case study in China.This research adopts a quantitative approach and collects primary data through a structured questionnaire distributed to HEYTEA customers. A total of 200 usable responses were analyzed using SPSS. The marketing mix variable was measured using 13 indicators based on the 7Ps framework, STP strategy was measured using 6 indicators, and customer satisfaction was measured using 5 indicators. Data analysis techniques included descriptive statistics, validity and reliability tests, classical assumption tests, multiple regression analysis, and hypothesis testing using t-tests and F-tests.The results indicate that both perceived marketing mix and STP strategies have a positive and significant effect on customer satisfaction. The marketing mix demonstrates a stronger influence, suggesting that product quality, service processes, store atmosphere, pricing fairness, and promotional effectiveness play a dominant role in shaping customer satisfaction. Meanwhile, STP strategies also significantly affect satisfaction, highlighting the importance of accurate market segmentation, focused targeting, and clear brand positioning in meeting customer needs and expectations. This study contributes theoretically by integrating marketing mix and STP strategies into a single empirical model to explain customer satisfaction in the context of China’s tea beverage industry. Practically, the findings provide valuable insights for HEYTEA’s management in refining marketing strategies to enhance customer satisfaction and maintain competitive advantage in an increasingly saturated market.